Prospects for Development of Integrated Beef Cattle and Cashew Farming in Muna Regency - Abdul Rizal; David Oscar Simatupang; Adrianus Adrianus; Anwar Anwar; Mani Yusuf; La Harudin; Hasriati Hasriati; Haerudin Tao (International Journal of Mechanical, Electrical and Civil Engineering, 2024)
The study aimed to find out the prospects of Development integrated farming business of beef cattle and cashew nuts. The study was carried out from March to May 2021. Respondents of the study consisted of beef cattle farmers who also grow cashew nuts. Sample of the location were determined purposively for a reason that not all sub districts are located in Muna regency, only a few out of 22 sub districts in total. Samples of sub districts and villages were selected purposively on a consideration that there were both beef cattle cattle and cashew nuts in the selected sub districts and villages. Samples of cattle breeders were determined with a random sampling, meaning that all breeders had equal opportunities to be selected. Data and the study were obtained by means of direct interviews, which were analyzed by Feasibility Tally Sheet. Based on the research results can be concluded. The research results show that integrated cattle and cashew farming has prospects for development with each rating, namely technical (7), economic (7), social (4), financial (4) and factors management (6) .